Cover Image. Issue 6 (June 2017) - Gupta, A.; Cole, S.; Labus, J. S.; Joshi, S.; Nguyen, T. J.; Kilpatrick, L. A.; Tillisch, K.; Naliboff, B. D.; Chang, L.; Mayer, E. A.
Abstract : The cover image, by A. Gupta et al., is based on the Original Article Gene expression profiles in peripheral blood mononuclear cells correlate with salience network activity in chronic visceral pain: A pilot study, DOI10.1111/nmo.13027 .